Jenis dan Fungsi Sapaan serta Persepsi Kesantunan dalam Interaksi di Kaunter Pertanyaan (Jurnal Bahasa, 2011)
The purpose of this article is to present findings concerning the types and functions of greetings and also perceptions of politeness in speech acts during interaction at an information counter. The study is based on the framework of Malay courtesy that anticipates greetings taking place at the start of a meeting or indeed at the start of any interaction. The study was carried out to investigate the extent of the practice of greeting at an information counter and to relate the concept of politeness in this context to phatic communication and communication competence. A particular information was selected for initial observation and was eventually selected for data collection. Greetings were collected by utilising a checklist that was developed from initial observation; perceptions were gathered from recordings of structured interviews with respondents chosen by convenience sampling. The main findings showed that greetings were not frequently exchanged at the information counter and that this was not because the speakers were lacking in communicative competence or awareness of Malay politeness. Rather, it was due to the place where the interactions occurred. The findings in this article contribute to the corpus of knowledge of Malay politeness in Malaysia.Keywords: greetings, politeness, phatic communication, communicative competence, context, perception